Roots of Sexual Abuse: A Pathway Model for Adolescents Who Offend - Newstrom, Nicholas P. (Journal of interpersonal violence, 2024)
Theoretical models implicate insecure attachment, peer isolation, hostile masculinity, and the use of sex for coping in sexual perpetration against children. This study builds on previous research and tests the direct and indirect effects of attachment, interpersonal and sexual control problems, and masculine adequacy to explain sex offending against children in adolescents. Structural equation modeling was used to conduct a path analysis using 464 adolescent males. A significant path model was fitted that identified three paths between anxious attachment, social isolation, sexual dyscontrol, masculine adequacy, and offending against a child. The model partially confirms previous research on adolescents who commit sexual abuse. The best fitting model indicates a direct path from anxious attachment to sexual offending against a child, but also indicates two indirect paths, where anxious attachment and committing child sexual abuse was partially mediated by social isolation and masculine adequacy, which, in turn, were negatively associated with each other, and a path including sexual dyscontrol, which was positively associated with both social isolation and masculine adequacy. The results suggest that commission of child sexual abuse by adolescent males is related to individual proclivities, social experiences, and attitudes toward sexuality and masculinity.